1995
DOI: 10.1136/vr.136.21.531
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of equine influenza among horses in Hong Kong during 1992

Abstract: Equine-2 influenza virus A (H3N8) infection occurred among vaccinated thoroughbred horses in Hong Kong during November and December 1992. The outbreak was unique in that it occurred among a large population stabled under intensive conditions. It resulted in the postponement of seven race meetings over a period of 32 days. The outbreak originated after the importation of horses 25 to 32 days before any clinical signs were reported. Vaccination did not prevent 75 per cent of the population from becoming infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 0 publications
1
79
0
Order By: Relevance
“…The occurrence of EI in these horses is notable, as it illustrates the risk of global virus spread through international movement of vaccinated horses. The role of subclinically infected horses in the international spread of EIV has been highlighted in recent years as has the significant economic losses involved following the introduction of EI into a naïve population 13, 35, 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of EI in these horses is notable, as it illustrates the risk of global virus spread through international movement of vaccinated horses. The role of subclinically infected horses in the international spread of EIV has been highlighted in recent years as has the significant economic losses involved following the introduction of EI into a naïve population 13, 35, 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…It would also appear that current quarantine strategies are often inadequate to prevent influenza infections from being transmitted between continents. Since the outbreak of equine influenza in Hong Kong in 1992, The Hong Kong Jockey Club has introduced more rigorous quarantine measures, including routine screening of imported horses for equine influenza virus using methods that can detect subclinical infections (Powell et al, 1995).…”
Section: I a / 6 3 A S K I I S W V S I V M I I M R T G K I P D T V mentioning
confidence: 99%
“…Although the homologous titer of the ferret antiserum raised to La Plata93 was 4 to 8 times lower than those of the other ferret antisera, the geometric mean HI antibody titer against La Plata93 of horses was higher than those against the other vaccine strains (Avesta93 and Ibaraki07). Powell et al [17] reported that the clinical morbidity rate of horses with an HI antibody titer of more than >40-80 or >80 was 10 or 0%, respectively, during the outbreak in Hong Kong in 1992. From these above, it is suggested that not only the Japanese vaccine strains possess the adequate immunogenicities in horses, but also they can induce an antibody reacting well with Richmond07.…”
mentioning
confidence: 99%